The imitative behaviour of children and chimpanzees: A window on the transmission of cultural traditions - Mark Nielsen (Revue de Primatologie)
Humans engage in a multitude of complex social activities that, depending on such things as shared history, proximity, language and identification, can be engaged in differently from one community to another. Humans are a cultural species: But we are not the only ones. An array of behaviours indicative of cultural variation has been identified in chimpanzees, our closest living relatives, that has yet to be found in any other nonhuman animal. However, the breadth and depth of these behaviours seem insignificant when compared to the profound cultural variation inherent in human social behaviour. The source of differences between humans and chimpanzees in the proliferation of cultural traditions may be attributed to differences in the way these species engage in imitation. Human children show a strong tendency to imitate the actions of others at the expense of producing the functional outcomes of those actions, a tendency that chimpanzees do not show. It is argued that this tendency is an outcome of young children’s motivation to be social and to interact with others, and it is this that has driven the proliferation of human culture.